Public Understanding, The Role of Local Actors, and Innovation in Collaboration to Alleviate Poverty in Tolitoli City - Iqbal, Muhammad; Nursifa; Zaskia (Teras Kampus, 2025)
This study uses a qualitative-explanatory approach to examine the interaction between public understanding, the role of local actors, and innovation in collaborative poverty alleviation in Tolitoli City. This study collected data through observations, in-depth interviews, focus group discussions (FGDs), and a review of policy documents, supported by quantitative analysis to ensure triangulation. The results indicate that collaborative poverty alleviation in Tolitoli remains hampered by pragmatic public understanding. Collaboration is viewed more as a channel for receiving aid than as a space for participation. Other obstacles include data inconsistencies, weak socialization, and low transparency. The role of local organizations, NGOs, and community leaders is crucial but suboptimal due to weak coordination and capacity constraints. Administrative and community innovations have also not been integrated due to procedural constraints and minimal documentation. This study applies the frameworks of Mulgan, Rogers, and Ansell & Gash to recommend improvements in data governance and transparency that enhance public understanding of collaborative objectives and to strengthen formal collaboration mechanisms that empower local actors. Complementary measures include technical training for facilitators and community leaders, documentation of community best practices, and the establishment of a collaborative working platform to integrate administrative and community innovations into an adaptive and sustainable intervention model.